2017
DOI: 10.5897/ajar2017.12785
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical characterization of prickly pear (Opunicia Ficus indica) in the semi-arid region of Bahia State, Brazil

Abstract: In Brazil, prickly pear has gained increasing attention, mainly due to its nutritional benefits of health promotion, however, its postharvest conservation is still incipient and has to be evaluated. The objective of this work was to evaluate the physical and physico-chemical characteristics of prickly pear from three municipalities in the semi-arid region of the state of Bahia-Brazil. The fruits were harvested at random at the commercial harvest point stage, when the bark began to show a change of color from g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…It measures the sweet-acid balance of foods. A high °brix/acidity ratio indicates there are more sugars than acids in the fruit (Nunes et al, 2017). The results in Table 3 showed that the °brix/acidity ratio in prickly pear pulp was 178.87.…”
Section: °Brix/acidity Ratiomentioning
confidence: 97%
See 3 more Smart Citations
“…It measures the sweet-acid balance of foods. A high °brix/acidity ratio indicates there are more sugars than acids in the fruit (Nunes et al, 2017). The results in Table 3 showed that the °brix/acidity ratio in prickly pear pulp was 178.87.…”
Section: °Brix/acidity Ratiomentioning
confidence: 97%
“…It could be because the fruit samples included were wild-grown and un-irrigated, as well as the low rainfall rate during this study in the regions where the prickly pear plants grow. Nunes et al (2017) reported that the weight of fruits that originated from high annual rainfall regions is higher than fruits from the lowest annual rainfall regions. When they were ready to be picked, the fruit and pulp of prickly pear plants that were given extra water or water from a business were bigger (Zegbe, 2020).These findings suggest that the low weight of fruits found in this study is likely due to environmental conditions, including limited water availability and wild growth, which have a significant effect on the production of prickly pear fruits.…”
Section: Physical Properties 311 Weight Of Fruit and Its Fractionsmentioning
confidence: 99%
See 2 more Smart Citations